Intramedullary Spinal Cord Metastasis in Spinal Ependymomas - Zanib Javed; Raheema Sadiq; Hania Fatima; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association)
Drop metastasis, or intramedullary spinal cord metastasis(ISCM), is a rare condition accounting 0.9%–5% of CNS orspinal metastases. It arises from tumour cell disseminationthrough cerebrospinal fluid (CSF), often affecting thethoracic and lumbar spine. Clinical features include rapidlyprogressive neurological deficits, limb weakness, sensoryloss, and pain. Diagnosing drop metastasis is challengingand MRI with gadolinium remains the gold standardmodality for investigation. Surgical resection followed byradiotherapy remains the primary treatment option,whereas chemotherapy serves a palliative role in cases ofrecurrence or disseminated metastases.